Enhancing Performance Through MSME Entrepreneurship, Product Innovation Capabilities and Competitive Advantage in Kudus Regency's Culinary Sector - Fadilasari, Miladia; Tae Ferdinand, Augusty (International Journal of Scientific Research and Management (IJSRM), 2023)
Research aims: This study is to determine performance improvement through MSME entrepreneurship, product innovation capabilities and competitive advantage in the culinary field of Kudus district.Design/Methodology/Approach: This research is a descriptive research. Data was collected from the population of MSME owners and actors in the culinary industry in Kudus Regency. Target sampling is done to target prospective respondents with certain characteristics. Respondent criteria are: Have a micro business that offers culinary products and has been established or operating for at least 1 year and the respondent has a minimum educational background of high school or equivalent. This research was conducted in Kudus Regency by involving 270 respondents. This study also explores factors that can affect business performance, namely: Entrepreneurial orientation, Product innovation capability, and Competitive advantage.Research findings: The results of the research show that based on the results of the research there are many things that can be considered important in the Entrepreneurship Orientation process, especially how culinary MSME actors in Kab. Kudus is able to be Entrepreneurial Oriented by cultivating its product innovation capabilities, so that it can create and make new improvements to the merchandise presented so that with continuously developing innovation it can create the right merchandise that is not easily imitated through competition so that someoneTheoretical contribution/Originality: The novelty of this study is that this test uses the Service Dominant Logic approach. Entrepreneurial Orientation is a multidimensional behavioral concept consisting of an innovation component, an opportunity-taking component, and a proactive attitude component. In the context of this study, there can be aggressive gains.Practitioner/Policy implication: Both the government and especially the Kudus area to better improve entrepreneurial performanceKeywords: MSME Entrepreneurship, Product Innovation Capability, and Performance ImprovementResearch aims: This study is to determine performance improvement through MSME entrepreneurship, product innovation capabilities and competitive advantage in the culinary field of Kudus district.Design/Methodology/Approach: This research is a descriptive research. Data was collected from the population of MSME owners and actors in the culinary industry in Kudus Regency. Target sampling is done to target prospective respondents with certain characteristics. Respondent criteria are: Have a micro business that offers culinary products and has been established or operating for at least 1 year and the respondent has a minimum educational background of high school or equivalent. This research was conducted in Kudus Regency by involving 270 respondents. This study also explores factors that can affect business performance, namely: Entrepreneurial orientation, Product innovation capability, and Competitive advantage.Research findings: The results of the research show that based on the results of the research there are many things that can be considered important in the Entrepreneurship Orientation process, especially how culinary MSME actors in Kab. Kudus is able to be Entrepreneurial Oriented by cultivating its product innovation capabilities, so that it can create and make new improvements to the merchandise presented so that with continuously developing innovation it can create the right merchandise that is not easily imitated through competition so that someoneTheoretical contribution/Originality: The novelty of this study is that this test uses the Service Dominant Logic approach. Entrepreneurial Orientation is a multidimensional behavioral concept consisting of an innovation component, an opportunity-taking component, and a proactive attitude component. In the context of this study, there can be aggressive gains.Practitioner/Policy implication: Both the government and especially the Kudus area to better improve entrepreneurial performance